Dileme transnacionalne civilne družbe - Rek, Mateja (Družboslovne razprave, 2006)
The author places the formation of transnational social spaces within the context of the changing role of nation states that are increasingly faced with impacts of globalisation. The focus is on individual engagements of local,regional, international and virtual actors (from political, civil society and economic spheres) who are entering the relationships of co-operative activities. By doing so, they are building, negotiating and dynamically changing transnational bonds. The analysis of transnational interconnectedness is narrowed down to the development of the transnational civil society in the context of the EU. The author draws attention to a series of conceptual end empirical difficulties arising in both scientific and policy areas in trying to decide on basic questions concerning the transnational civil society in the EU, like: Who are the actors involved in civil engagements at the EU level? What is their role? How do we find suitable mechanisms within the EU bodies that would give civil society actors the status of legitimate partners in the processes of EU governance?
Keywords: Transnacionalizem; Transnationalism; Nacionalna država; National state; Globalisation; Globalizacija; globalization; Civil society; Civilna družba; European Union; Evropska unija